1997
DOI: 10.1097/00004032-199707000-00001
|View full text |Cite
|
Sign up to set email alerts
|

A Brief History of People and Events Related to Atomic Weapons Testing in the Marshall Islands

Abstract: The events related to nuclear testing in the Marshall Islands began at the end of WWII when the U.S. began an initiative to determine the effect of nuclear weapons on naval vessels and on the performance of military personnel. The first tests took place in 1946 even though the area known as Micronesia was not entrusted to the U.S. by the United Nations until 1947. Beginning with the first relocation of the Bikini people to Rongerik Atoll in 1946, the saga of the Marshall Islands involvement in the atomic age b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 8 publications
0
45
0
1
Order By: Relevance
“…Both nutrient enrichment and high fishery pressure are perceived concerns on Majuro Atoll, as residents place a strong reliance upon the urban center and marine resources for livelihoods and income generation (Pinca et al 2005, Beger et al 2008. In contrast, Rongelap Atoll has remained largely uninhabited for 57 yr due to impacts associated with atomic bomb testing at Bikini Atoll in 1954 (Simon 1997). Currently, major clean-up efforts have been completed, and a resettlement process has begun.…”
Section: Study Region and Sampling Designmentioning
confidence: 99%
“…Both nutrient enrichment and high fishery pressure are perceived concerns on Majuro Atoll, as residents place a strong reliance upon the urban center and marine resources for livelihoods and income generation (Pinca et al 2005, Beger et al 2008. In contrast, Rongelap Atoll has remained largely uninhabited for 57 yr due to impacts associated with atomic bomb testing at Bikini Atoll in 1954 (Simon 1997). Currently, major clean-up efforts have been completed, and a resettlement process has begun.…”
Section: Study Region and Sampling Designmentioning
confidence: 99%
“…Anita has written an overview of colonialism and the bomb in the Pacific. There are a number of descriptive narratives of the Marshall Islands tests (Kiste 1974;Weisgall 1994;Carucci 1997;Simon 1997;Barker 2004;de Groot 2006) (Mason 1950(Mason , 1954 and recent articles that contextualise the Bikinian's historical experience read from different, including geographic and folkloric, perspectives (Davis 2005a(Davis , 2005bMcArthur 2008). A description of the terrestrial material traces of nuclear testing on Bikini Atoll can be found in Brown (2013).…”
Section: Bombs and Bikinismentioning
confidence: 99%
“…The Japanese fishing boat Fukuryu Maru, or Lucky Dragon, located about 150 km east of Bikini was also contaminated with Bravo fallout. Despite the hope-giving name of the vessel, all 23 crewmembers suffered from radiation sickness, and one member later died of liver and blood damages (Simon, 1997, Eisenbud, 1997. 6 hours after the Bravo test Air weather service personnel situated on Rongerik, about 300 km east of Bikini, found their gamma monitors to peak at their limit value of 1 mSvh -1 (Cronkite et al, 1997).…”
Section: The Castle Bravo Incidentmentioning
confidence: 99%
“…People on the Rongelap atoll and the Ailinginae atoll were evacuated about 50 hours after the Bravo fallout reached Rongelap, on 3 March. People on the Utrik atoll were evacuated on 4 March (Simon, 1997). Estimation on the mean whole-body external dose to persons on Rongelap is 1.75 Gy.…”
Section: The Castle Bravo Incidentmentioning
confidence: 99%